Abandoned Children - Brown, Helen (Labour / Le Travail, 2001)
The article reviews the book, "Abandoned Children," edited by Catherine Panter-Brick and Malcolm T. Smith.

Women Teachers and Feminist Politics 1900-39 - Brown, Helen (Labour / Le Travail, 1999)
The article reviews the book, "Women Teachers and Feminist Politics 1900-39," by Alison Oram.